Occurrence and characterization of Escherichia coli ST410 co-harbouring blaNDM-5, blaCMY-42 and blaTEM-190 in a dog from the UK - Reynolds, M; Phan, H; George, S; Hubbard, A; Stoesser, N; Maciuca, I; Crook, D; Timofte, D (Oxford University Press, 2019)
Background/Objectives:Carbapenemase-producing Enterobacteriaceae (CPE) are a public health threat, and have been found in humans, animals and the environment. Carbapenems are not authorized for use in EU or UK companion animals, and the prevalence of carbapenem-resistant Gram-negative bacilli (CRGNB) in this population is unknown. Methods:We investigated CRGNB isolated from animal specimens received by one diagnostic laboratory from 34 UK veterinary practices (September 2015-December 2016). Any Gram-negative isolates from clinical specimens showing reduced susceptibility to fluoroquinolones and/or aminoglycosides and/or cephalosporins were investigated phenotypically and genotypically for carbapenemases. A complete genome assembly (Illumina/Nanopore) was generated for the single isolate identified to investigate the genetic context for carbapenem resistance. Results:One ST410 Escherichia coli isolate [(CARB35); 1/191, 0.5%], cultured from a wound in a springer spaniel, harboured a known carbapenem resistance gene (blaNDM-5). The gene was located in the chromosome on an integrated 100 kb IncF plasmid, also harbouring other drug resistance genes (mrx, sul1, ant1 and dfrA). The isolate also contained blaCMY-42 and blaTEM-190 on two separate plasmids (IncI1 and IncFII, respectively) that showed homology with other publicly available plasmid sequences from Italy and Myanmar. Conclusions:Even though the use of carbapenems in companion animals is restricted, the concurrent presence of blaCMY-42 and other antimicrobial resistance genes could lead to co-selection of carbapenemase genes in this population. Further studies investigating the selection and flow of plasmids carrying important resistance genes amongst humans and companion animals are needed.